KONTRIBUSI DAN KENDALA PELAKSANAAN APIKULTUR DI DESA PENDUA KABUPATEN LOMBOK UTARA - Maya, I Putu Angga Teja; Wahyuningsih, Endah; Hidayati, Eni (JURNAL RIMBA LESTARI, 2022)
The utilization of land use value is crucial in light of limited availability. One way to maximize it is by integrating animal husbandry, such as beekeeping, which is currently being developed in North Lombok Regency, particularly in Pendua Village. This study aims to determine the contribution of Trigona sp. bee honey, the obstacles to implementing apiculture, and potential solutions. Purposive sampling was used to collect data from 26 apiculture yards, and data were collected through interviews and questionnaires. The study's findings revealed that Trigona sp. bee honey is valued at Rp. 150,000 per 600 ml. Obstacles encountered included feed availability, pest attacks, farmer expertise, theft, and earthquakes. Potential solutions include feed enrichment and renewal, training and coaching, bee farmer groups, and pest control.